PRODUCTIVITY OF PADDY-POTATO-WHEAT SYSTEM IN HARYANA - Singh, Jage; Khurana, S C (Potato Journal, 2013)
Productivity of paddy-potato-wheat system was studied during 3rd and 4th year in an experiment consisting of combinations of 2 crop duration for potato and 5 fertilizer doses to wheat at RRS, CCS HAU, Karnal. Yield of potato cv. Kufri Ashoka increased significantly from 219.3 to 245.4 q/ha with the increase in crop duration from 80 to 90 days. Wheat yield ranged from 31.07 to 36.81 q/ha (mean for 2 years) and was significantly higher where potato crop was harvested at 80 days. Wheat crop showed significant response to the fertilizer doses given to it. Fertilizer doses given to wheat crop did not influence the yield of potato. However, it affected the yield of paddy following wheat in the cropping system during one of the two years of investigation. Yield of paddy ranged from 66.15 to 72.78 q/ha (mean for 2 years).